2021
DOI: 10.1111/ajco.13545
|View full text |Cite
|
Sign up to set email alerts
|

Increased TOX expression concurrent with PD‐1, Tim‐3, and CD244 in T cells from patients with non‐Hodgkin lymphoma

Abstract: Aim: To characterize immune suppression in lymphoma, thymocyte selectionassociated high mobility group box protein (TOX) expression and co-expression with programmed cell death receptor-1 (PD-1), T cell immunoglobulin mucin-domaincontaining-3 (Tim-3), and CD244 in CD3+, CD4+, CD8+, and regulatory T (Treg) cells from patients with lymphomas were analyzed.Methods: TOX expression and co-expression with PD-1, Tim-3, and CD244 in CD3+, CD4+, Treg, and CD8+ T cells were analyzed by multi-color fluorescent flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…In this study, we examined the characteristics of TOX in T cell subsets and found a significantly increased percentage of TOX+ CD3+, CD4+, and CD8+ T cells in PB from AML patients. This result is consistent with findings of upregulation of TOX in solid tumors and lymphomas (Huang et al, 2021; Kim et al, 2020; Liang, Zhao, et al, 2021; Wang et al, 2019; Yang et al, 2021). TOX+CD244+, TOX+PD‐1+, and TOX+Tim‐3+ double‐positive T cells were evidently increased in the CD3+, CD4+, and CD8+ T cell populations, suggesting that TOX may play a vital role as a transcription factor in the formation of exhaustive T cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, we examined the characteristics of TOX in T cell subsets and found a significantly increased percentage of TOX+ CD3+, CD4+, and CD8+ T cells in PB from AML patients. This result is consistent with findings of upregulation of TOX in solid tumors and lymphomas (Huang et al, 2021; Kim et al, 2020; Liang, Zhao, et al, 2021; Wang et al, 2019; Yang et al, 2021). TOX+CD244+, TOX+PD‐1+, and TOX+Tim‐3+ double‐positive T cells were evidently increased in the CD3+, CD4+, and CD8+ T cell populations, suggesting that TOX may play a vital role as a transcription factor in the formation of exhaustive T cells.…”
Section: Discussionsupporting
confidence: 91%
“…Cell surface staining analysis for PD‐1, Tim‐3, CD244, CD25, CD3, CD4, CD8, and CD45 and intranuclear staining analysis for TOX and FoxP3 were performed with a BD FACS Canto flow cytometer (BD Biosciences, San Jose, USA) and Flowjo software (Flowjo LLC, USA) as previously described (Huang et al, 2021; Kasakovski et al, 2021). The antibodies used for this study were purchased from BD Biosciences (San Jose, USA) and eBioscience (San Diego, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the association between TOX and PD-1 or CTLA-4 co-expression only occurs in T cells (21) and not PBMCs, which include a high percentage of AML cells. We found that TOX genes are also expressed in AML cell lines and primary AML cells (data not shown), which suggests that there are different patterns of expression for TOX genes in T cells and AML cells, which may play a different role.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we found higher TOX expression concurrent with PD-1, Tim-3, or CD244 in T cells from patients with B cell non-Hodgkin's lymphoma (B-NHL), which suggested that TOX may be involved in inducing CD8+ T cell exhaustion by co-regulation with immune checkpoint proteins (21).…”
Section: Introductionmentioning
confidence: 93%